In terms of skills of oral communication Turkish language and literature education [Sözlü i̇leti̇şi̇m beceri̇leri̇açisindan Türk di̇li̇ve edebi̇yati eǧi̇ṫiṁi] - (:unkn) unknown (My University, 2006)
In this study, the role of literature education which help people to acquire skills of oral communication which are crucial to the information age men was examined. In this respect first of all communication, elements of communication, oral communication, and the importance of oral communication for individual and community were stressed. Later on some responses are seeked for the questions of "What is the effect of literature programme in achieving oral skills and How should the current literature programme be? after doing some researches and examined articles written in this field. The following points are suggested on how literature teachers should be and how they should be trained, considering the fact that if the teacher is not qualified enough and how effective the programme is, the expectations would not be sufficient enough. • Turkish Literature Curriculum education be revised according to the student centered education mentality. And student-teacher relation should be taken into consideration when forming the goals of Turkish Literature Teaching Curriculum. • The level of standard skill which students are requested to achieve should be determined. And the level of teaching and learning activities during classes should be in the way to achieve the mentioned level. • The content and goals of the course should be meaningful and trustable. • The methods and techniques which will be intended to use should provide effective participation students' learning-teaching process. • When measuring and assessing in addition to traditional methods, alternative ones should also be used. • When choosing students for the departments of Turkish Literature and Languange and employing them as teachers, personal qualities, academic achievement and communication abilities should be taken into consideration as well as the exam grade (OSYM).
Keywords: Literature education; Literature teacher; Oral communication; The Turkish Language and Literature Curriculum